Comparison between autologous noncultured extracted hair follicle outer root sheath cell suspension and autologous noncultured epidermal cell suspension in the treatment of stable vitiligo: a randomized study. (13th August 2013) - Singh, C.; Parsad, D.; Kanwar, A.J.; Dogra, S.; Kumar, R.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Noncultured epidermal cell suspension (NCES) is emerging as the first line of surgical management of stable vitiligo. Recently, noncultured extracted hair follicle outer root sheath cell suspension (NCORSHFS) has been shown to be effective in surgical treatment of vitiligo. As the hair follicle is an important reservoir of melanocytes and their precursor cells, this seems to be an important technique of replenishing melanocytes to depigmented patches. What does this study add? This is the first randomized study to compare two cellular techniques of surgical management of vitiligo. We have shown that both NCES and NCORSHFS are safe and effective techniques with comparable efficacy.